Geography Master's Knowledge of Learning Models that Can Establish Islamic Spatial Character Students in SMA Negeri Kabupaten Lombok Timur, Indonesia - Afriza, Zulti (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this research is to analyze the teacher's knowledge about the learning model that can shape the spatial character of Islamic students and analyze the students' Islamic character in the geography learning model at SMA Negeri in Kabupaten Lombok Timur. This type of research uses a qualitative approach. Technique of collecting data by observation, interview and documentation, research instrument is researcher own. Technique Data analysis in this research is done with Miles and Huberman model. The result of the research shows that Jigsaw learning model can shape the spatial character of the Islamic student. The Islamic characters formed in the Jigsaw learning model are teamwork, caring, respectful of others' opinions, responsible, and independent. Islamic spatial character is not littering, planting trees as a form of environmental preservation, not picking flowers in the school environment.